Conflict of Law Culture Consequence Law Transplantation in Indonesia Money Laundry Regulation - July Esther (LEGAL BRIEF, 2022)
Legal Transplantation in eradication criminal law money laundering framework in Indonesia for the first time was did in 2002 with legislated Law No. 15 of 2002 on Money Laundering and Eradication Money Laundering and then in October 2003 amendment with Law No. 25 of 2003 and then regulated in Law No. 8 of 2010 on Prevention and Eradication Money Laundering Crime. Legal transplantation is carried out by incorporating international standards into the national legal system, particularly into Law of Money Laundering and Eradication Money Laundering. In addition, legal transplantation was also carried out under the pressure of Financial Action Task Force (FATF) which resulted from the assumption that Indonesia has not fully obeyed 40 Recommendations and 9 Special Recommendations from FATF. The type of research used is doctrinal legal research or normative legal research, namely legal research using secondary data sources whose emphasis on theoretical and analytical qualitative. Based on the results of research due to legal transplantation resulted in a conflict of legal value in the criminal law system in Indonesia which is oriented to "follow the suspect" rather than "follow the money" especially in law enforcement anti money laundering regime. Likewise has resulted in a legal culture clash which is a reflection of the legal discipline of socio-political aspects.